Development of Interactive Powerpoint Learning Media Based on Guided Inquiry on Class XI High School Chemical Equilibrium Material - Tifani Qairani Fitri; Syamsi Aini (Universitas Riau, 2023)
Learning media is one of the supporting factors for achieving learning objectives. One of the learning media used is Powerpoint media. the type of research used is research and development or Research and Development (R&D). This study aims to develop a guided inquiry-based powerpoint interactive learning media on chemical equilibrium material and reveal its validity and practicality as a chemistry learning medium. The development model used in this study is a 4-D model (define, design, develop and disseminate). The stages that are carried out are only up to the develop stage. The study was conducted at SMAN 2 Lubuk Basung. The learning media developed were assessed by 9 validators, and practicality was assessed by 2 chemistry teachers and 27 students of class XII MIPA. Based on the research that has been carried out, it is found that the content validation and construct validation of the learning media developed have a high validity category with the Aiken's V formula of 0.90399 and 0.92857 and the practicality of learning media based on the practicality questionnaire of the teacher's response is 91.05556 and student responses of 94.2469 with very practical category.